Implementation of PMO in the state secretariat of infrastructure and mobility of Santa Catarina - Junior, Hélio Mondardo; Vasconcellos , Jaqueline de; Pereira, Joney Carlos; Bianchet , Luana; Schlosser, Luciano Henry; Bonfatti , Talitha Roberta (Seven Editora, 2023)
Project management in public administration faces major challenges. This article deals with the general bases of its operation, specifically in the Government of the State of Santa Catarina. It then elucidates how the Project Management Office of the State Public Administration of the Executive Branch of Santa Catarina (EPROJ) and the Project Nuclei took place, especially the State Secretariat for Infrastructure and Mobility, in the figure of PMO. It subsequently analyzes the general methodological basis of project management used by EPROJ and how it was applied in the training of specialists hired for project management of the nuclei in the multiplication of this methodology in relation to SIE servers. Finally, it illustrates the challenges and successes experienced throughout this process and brings suggestions for its improvement. DOI:https://doi.org/10.56238/alookdevelopv1-079